2018
DOI: 10.3390/ijms19010156
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Evolution of European Bat Lyssavirus 2

Abstract: Bat rabies cases in Europe are mainly attributed to two lyssaviruses, namely European Bat Lyssavirus 1 (EBLV-1) and European Bat Lyssavirus 2 (EBLV-2). Prior to the death of a bat worker in Finland in 1985, very few bat rabies cases were reported. Enhanced surveillance in the two subsequent years (1986–1987) identified 263 cases (more than a fifth of all reported cases to date). Between 1977 and 2016, 1183 cases of bat rabies were reported, with the vast majority (>97%) being attributed to EBLV-1. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 58 publications
4
22
0
Order By: Relevance
“…Daubenton's bat (Myotis daubentonii) is the main reservoir of EBLV-2 [4], and EBLV-2 cases in bats were reported from several European countries [7]. Thus far, lyssaviruses reported from Poland were characterized as EBLV-1 or BBLV [8].…”
Section: Discussionmentioning
confidence: 99%
“…Daubenton's bat (Myotis daubentonii) is the main reservoir of EBLV-2 [4], and EBLV-2 cases in bats were reported from several European countries [7]. Thus far, lyssaviruses reported from Poland were characterized as EBLV-1 or BBLV [8].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen cases of European bat lyssavirus type 2 (EBLV-2) have been detected in Daubenton's bats (Myotis daubentonii) in the UK, the first in 1996 and the most recent in 2017. Sero-surveillance has demonstrated a seroprevalence in the UK of up to 4% 14,[20][21][22] . Daubenton's bats are widespread temperate insectivorous bats with a range from Europe to Japan 23 .…”
mentioning
confidence: 99%
“…Similarly, there are also large geographic distances between the German and French isolates within the different BBLV lineages A and B (Eggerbauer et al, ). This is different to EBLV‐2, where there is strong geographical clustering of lineages across Europe (McElhinney et al, ), although with such a small number of EBLV‐2 and BBLV cases reported such conclusions are considered preliminary.…”
Section: Comparison Of Nucleotide Sequence Identity Values (%) For Nmentioning
confidence: 74%
“…In Europe, the vast majority of reported bat rabies cases have been characterized as European bat lyssavirus 1 (EBLV‐1), associated with Serotine bats ( Eptesicus serotinus , Eptesicus isabellinus ). European bat lyssavirus 2 (EBLV‐2) isolated mostly from Daubenton's bats ( Myotis daubentonii ) has also been reported in many European countries (McElhinney et al, ). In addition, single cases of rabies in bats have been reported: West Caucasian bat virus (WCBV) (Kuzmin, Hughes, Botvinkin, Orciari, & Rupprecht, ), Lleida bat lyssavirus (LLEBV) and Kotalahti bat lyssavirus (KBLV) (Aréchiga Ceballos et al, ; Nokireki, Tammiranta, Kokkonen, Kantala, & Gadd, ) in the West Caucasus, on the Iberian peninsula and Finland, respectively.…”
Section: Comparison Of Nucleotide Sequence Identity Values (%) For Nmentioning
confidence: 99%